Mediating Effect of Spiritual Attitude and Involvement on the Relationship Between Self-Esteem and Psychological Well-Being Among LET Examinees - Leo Lestere Mollaneda Tao-Tao (Nazhruna: Jurnal Pendidikan Islam, 2022)
In this study, the main prod was to investigate another aspect to which spiritual attitude and involvement were the mediating variables for the researcher's interest. This study was a descriptive correlation structure in the way of descriptive, non-experimental research technique. The study was conducted at General Santos City with 294 respondents. Using cluster sampling was applied from the list of registered examinees with elementary and secondary baccalaureate degree holders. Questionnaires were adapted: the Coopersmith Self-Esteem Adult 58 item version, Ryff's Psychological Well-Being Scales (PWB) 42 item version, and Spiritual Attitude Involvement List scale. Hence, the mean, Pearson correlation coefficient, and regression analysis were utilized to arrive at a valid result. The result was positive significant (p<0.05) with the relationship between self-esteem and psychological well-being. Also, a significant result of the interaction of the mediating variable of spiritual attitude and involvement is the Licensure Examination for Teachers examinees' variables.